Early Childhood Teachers’ Content Knowledge on Green Growth Education - 양재민; 김상림 (International Journal of Advanced Culture Technology(IJACT), 2019)
The purpose of the study was to examine early childhood teachers’ content knowledge on green growth education. The subjects, 45 early childhood teachers, were asked to draw concept maps about early childhood green growth education. Their concept maps were analyzed in terms of superordinate and subordinate concepts by contents and frequencies. The results showed that early childhood teachers used 182 superordinate and 1,292 subordinate concepts in the concept map of green growth education for young children. Although early childhood teachers had a wealth of content knowledge on green growth education as proposed by the Ministry of Education, their knowledge was disproportionate to some areas and sub-areas of green growth education. These results implied the needs of developing teacher education programs for early childhood green growth education.